2002
DOI: 10.1095/biolreprod66.3.718
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Osteopontin at the Maternal-Placental Interface in Pigs1

Abstract: Noninvasive, epitheliochorial placentation in the pig follows a prolonged preimplantation period characterized by migration, spacing and elongation of conceptuses, and secretion of estrogen for maternal recognition of pregnancy. Osteopontin (OPN) is an extracellular matrix protein that binds integrins to promote cell-cell attachment and communication. OPN appears to play a key role in conceptus implantation and maintenance of pregnancy in sheep; however, a role for OPN in the porcine uterus has not been establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
139
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(158 citation statements)
references
References 45 publications
13
139
2
1
Order By: Relevance
“…In the present experiment, Western blot analysis with an antiserum against human OPN identified 3 immunoactive bands at 70, 12, and 9 kDa. A 70-kDa form of OPN has been reported in uterine flushings in the pig (Garlow et al, 2002) and appears to be homologous to SP-1, a stallion seminal plasma osteopontin (Brandon et al, 1999). Although the 70-kDa osteopontin species identified in the present study of boar seminal plasma is homologous to the bull (55 kDa) and stallion (70 kDa) OPN forms, the relative amount of OPN-70 did not differ among boars.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…In the present experiment, Western blot analysis with an antiserum against human OPN identified 3 immunoactive bands at 70, 12, and 9 kDa. A 70-kDa form of OPN has been reported in uterine flushings in the pig (Garlow et al, 2002) and appears to be homologous to SP-1, a stallion seminal plasma osteopontin (Brandon et al, 1999). Although the 70-kDa osteopontin species identified in the present study of boar seminal plasma is homologous to the bull (55 kDa) and stallion (70 kDa) OPN forms, the relative amount of OPN-70 did not differ among boars.…”
Section: Discussioncontrasting
confidence: 41%
“…OPN has been detected in both female Garlow et al, 2002) and male (Cancel et al, 1999;Rodríguez et al, 2000;Luedtke et al, 2002) reproductive tracts. OPN has been identified as a seminal plasma protein that is positively associated with fertility in the bull (55 kDa, pI 4.5) (Cancel et al, 1997(Cancel et al, , 1999 and the stallion (SP-1, 72 kDa, pI 5.6) (Brandon et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…More recently it has been detected in many tissues and fluids, including urine (Sorenson et al 1995), milk (Sorensen & Petersen 1993, Sorensen et al 2003, kidney (Xie et al 2001), uterine endometrium of rabbits (Apparao et al 2003), sheep (Johnson et al 2003, Kimmins et al 2004, cows (Kimmins et al 2004) and pigs (Garlow et al 2002), the bovine oviduct (Gabler et al 2003), and on the luminal surfaces of epithelial cells of human gastrointestinal and reproductive tracts, gall bladder, pancreas, lung, breast, urinary tract, salivary glands, and sweat glands (Brown et al 1992). OPN may be glycosylated, phosphorylated and sulfated, and its expression and post-translational modifications are tissue-specific and regulated by many hormones and growth factors (Denhardt & Guo 1993).…”
Section: Introductionmentioning
confidence: 99%
“…During the mid-to late-secretory phase of the menstrual cycle, OPN has been identified on the apical surface of uterine luminal and glandular epithelial cells, particularly in the vicinity of pinopodes (Quenby et al, 2007). The expression of OPN subsequently extends into the decidualizing stroma and embryonic trophectoderm (Omigbodun et al, 1997;Quenby et al, 2007), a distinctive pattern of events that has also been identified in other mammals, including pigs, rabbits, and sheep (Johnson et al, 1999(Johnson et al, , 2003bGarlow et al, 2002;Apparao et al, 2003;White et al, 2005). Moreover, while knockout OPN mice are fertile, they exhibit reduced pregnancy rates during mid-gestation, suggesting peri-implantation pregnancy loss (Weintraub et al, 2004), highlighting a functional role for OPN during pregnancy.…”
Section: Osteopontinmentioning
confidence: 88%